Weight-related shame and guilt, intuitive eating, and binge eating in female college students. (April 2019) - Craven, Michael P.; Fekete, Erin M.
Abstract: Shame and guilt are associated with greater eating disorder symptomatology, including binge eating. These emotional states may be related to binge eating as a result of one's attempt to use food as a means of coping. Little research has examined associations between weight-specific negative emotions and eating behaviors. Even less research has examined the role of intuitive eating as a mitigating factor of these associations. This study examined the relationships among weight-related shame and guilt and binge eating symptomatology in a sample of 196 undergraduate women. Further, we assessed the role of intuitive eating as a moderator of these relationships. Female college students completed an online questionnaire assessing demographics, weight-related shame and guilt, intuitive eating, and binge eating. After accounting for covariates, including body mass index, multiple regression analyses revealed that weight-related shame and guilt were related to increased binge eating symptomatology. Further, intuitive eating attenuated the relationship between weight-related shame and binge eating, but not between weight-related guilt and binge eating. Intuitive eating may be a protective factor for women experiencing weight-related shame. Highlights: Weight-related guilt is associated with greater binge eating symptomology in women. Weight-related shame is associated with greater binge eating symptomology in women. Intuitive eating attenuates the relationship between weight-related shame and binge eating.